2019
DOI: 10.17576/3l-2019-2503-10
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Blended In-service Teacher Professional Training on EFL Teacher Creativity and Teaching Effectiveness

Abstract: Current seminal studies on teacher creativity and teaching effectiveness have been widely investigated by numerous researchers. Most of them explored both variables (teacher creativity and effectiveness) from various aspects such as the perspectives of teachers, learners, and of gender but they failed to address one important variable, namely the influence of professional development background on these variables. Consequently, this study aims to analyse the influence of blended teacher professional training o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 25 publications
4
32
1
2
Order By: Relevance
“…These were done so as to understand and to know more about teacher cognition; teacher's knowledge that influences instructional practices. Yin (2014;1989, p.82), for example, looked at case study as a suitable research approach because through the process of describing, explaining, evaluating and predicting they (studies) will be able to "reveal the multiplicity of factors [which] have interacted to produce the unique character of the entity that is the subject of study." Such qualitative technique helps to unravel teacher cognition in actual classroom context.…”
Section: Methodology Designmentioning
confidence: 99%
“…These were done so as to understand and to know more about teacher cognition; teacher's knowledge that influences instructional practices. Yin (2014;1989, p.82), for example, looked at case study as a suitable research approach because through the process of describing, explaining, evaluating and predicting they (studies) will be able to "reveal the multiplicity of factors [which] have interacted to produce the unique character of the entity that is the subject of study." Such qualitative technique helps to unravel teacher cognition in actual classroom context.…”
Section: Methodology Designmentioning
confidence: 99%
“…While many studies on blended instructional design in the area of English Language teaching and learning can be found in the literature, the study related to the use of blended teaching and learning for teacher professional development programs has been scarce. Arifani et al, (2019) analysed how English teachers' creativity and effectiveness were influenced by blended teaching professional training. Involving 120 secondary school teachers in a survey study, they found that a positive influence was noted, with a notable increase in the teaching creativity and effectiveness especially in the aspects of teachers' knowledge of the subject matter, independent learning, and the learning environment and materials.…”
Section: Blended Professional Developmentmentioning
confidence: 99%
“…Maintaining the harmony of those two teaching proficiencies (proficient in the traditional and online teaching) becomes pertinent in today's digital era. Due to the growing demands of EFL teachers on these two competencies, many institutions that prepare English language teachers are competing to organize EFL teachers' training models using a blended approach for two main reasons (Arifani, Khaja, Suryanti, & Wardhono, 2019;Belland, Burdo, & Gu, 2015;Wong, 2019). First, technological development demands EFL teachers to be able to teach English using media to anticipate the shift of learning models from the traditional to online the learning model.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations